The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.59615/ijie.2.3.42
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Key performance indicators in Blockchain-Based Supply Chain Financing: Case Study of Chain Stores

Abstract: In recent years, due to the growth and development of financing tools and methods, financial institutions are always looking for new, efficient, and low-cost methods. In carrying out their daily production operations, companies are faced with different and diverse financial input and output flows from purchasing orders and inventory to receiving the price of sold goods, which are not the same in terms of time. Therefore, they will inevitably look for the financing of these processes, which is referred to as wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The results of the optimization have shown that in all three mentioned models, more weight in the investment portfolio has been allocated to industries that have less fluctuations in the stock returns of those industries. Also, the optimal weight has been decreasing over time for industries whose efficiency fluctuations have increased, and on the contrary, if the fluctuations in efficiency have decreased over time, the optimal share of the portfolio has increased [12]. Some other researchers focused on the optimization of the investment portfolio using the multivariable Markowitz and multivariate model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the optimization have shown that in all three mentioned models, more weight in the investment portfolio has been allocated to industries that have less fluctuations in the stock returns of those industries. Also, the optimal weight has been decreasing over time for industries whose efficiency fluctuations have increased, and on the contrary, if the fluctuations in efficiency have decreased over time, the optimal share of the portfolio has increased [12]. Some other researchers focused on the optimization of the investment portfolio using the multivariable Markowitz and multivariate model.…”
Section: Literature Reviewmentioning
confidence: 99%